The fabulous world of Faberge (A&E Television Network ; distributed by New Video Group, 1997)
Tells the complete story of the master jeweler's life, from his rise to international fame to his narrow escape from a Bolshevik firing squad. Jewelry experts explain why Faberge's rare eggs are still some of the most coveted art objects in the world.